ACTIVATON AND CHARACTERIZATION OF NATURAL ZEOLITE USING NaOH - Sumarni, Sumarni; Hindryawati, Noor; Alimuddin, Alimuddin (JURNAL ATOMIK, 2018)
A study on the activation of natural zeolite using NaOH and it’s application for adsorption Rhodamin B from waste liquid woven Samarinda has been conducted. The activation process was conducted by several steps namely, sample preparation and activation stage using NaOH with ultrasonic assisted, then characterized using X-Ray Flourescence (XRF), X-Ray Diffraction (XRD). The XRF analysis result showed that indicates a decrease of SiO2 54.359% in natural zeolite after activation with 6 M NaOH. The XRD analysis result showed the type of natural zeolite activated NaOH was mordenit with chemical compound Ca2.5Na2Al7.Si41O96.24H2O. The optimum condition on the adsorpsi of Rhodamin B from waste liquid woven Samarinda using activated zeolite at 6 M NaOH 60 minutes and with persen adsorpsi was 87.487 % and on the adsorbent weight of 1.25 gram with persen adsorption 82.311 %.